Exploring the channels of transmission between external debt and economic growth: Evidence from sub-Saharan African countries - Adewale Hassan; Daniel Meyer (Economies, 2021)
This study aimed to determine the channels through which external debt transmits its impact on economic growth in sub-Saharan African (SSA) countries. To this end, panel data comprising 30 SSA countries were investigated for the period 1985-2019, using the system generalized method of moments (GMM) estimation technique. The study identified public investment, private investment and total factor productivity as channels transmitting the non-linear effect from external debt to economic growth. Furthermore, the interest rate was also confirmed as a channel but with a direct effect. Contrariwise, the estimates indicated that savings are not a channel of transmission from external debt to economic growth in SSA. These findings call for urgent action from SSA countries to reduce their external debt stocks and implement alternative macroeconomic non-debt strategies to improve the identified channels to counteract the negative effect of high external debt on them.
Keywords: 330; economic growth; channels of transmission; external debt; sub-Saharan African countries